Studies on the history of late antique and Christian Nubia - Kirwan, Laurence, author. Link
1 online resource (302 pages)
Keywords: Gathered together here are the fruits of 60 years of research by the late Sir Laurence Kirwan into the history and archaeology of the mid 1st millennium AD in the Middle Nile Valley, papers previously scattered through a wide range of publications. Kirwan's fieldwork in the region, undertaken between 1929 and 1936, kindled a life-long interest in the transition from the pagan Kushite kingdom to the medieval Nubian states of Nobadia, Makuria and Alodia (Alwa) and of their conversion to Christianity in the 6th century AD. The 25 studies, one published here for the first time, were often of seminal importance when they first appeared, the author being exemplary in his use of the written sources to elucidate the archaeological data. As the preface by the editors shows, the views expressed remain fundamental to modern scholarship, offering valuable insights into this still relatively obscure period of transition from the ancient to the medieval world.